Extracellular circulating viral microRNAs: current knowledge and perspectives - Lagana', Alessandro; Russo, Francesco; Veneziano, Dario; Di Bella, Sebastiano; Pulvirenti, Alfredo; Giugno, Rosalba; Croce, Carlo M.; Ferro, Alfredo (Frontiers in Genetics, 2013)
MicroRNAs (miRNAs) are small non coding RNAs responsible of post-transcriptional regulation of gene expression through interaction with messenger RNAs (mRNAs). They are involved in important biological processes and are often dysregulated in a variety of diseases, including cancer and infections. Viruses also encode their own sets of miRNAs, which they use to control the expression of either the host's genes and/or their own. In the past few years evidence of the presence of cellular miRNAs in extracellular human body fluids such as serum, plasma, saliva, and urine has accumulated. They have been found either cofractionate with the Argonaute2 (Ago2) protein or in membrane-bound vesicles such as exosomes. Although little is known about the role of circulating miRNAs, it has been demonstrated that miRNAs secreted by virus infected cells are transferred to and act in uninfected recipient cells. In this mini review we summarize the current knowledge on viral circulating miRNAs and provide a few examples of computational prediction of their function.